(untitled) (American Journal of Islam and Society, 2015)
To appreciate North York’s newly opened Aga Khan Museum (AKM), one must first understand its patron, as this undertaking is only the most recent in a long line of proactive institutions and projects initiated by the Aga Khan all over the world. The Aga Khan and members of his family have cultivated this collection for decades, and have given it a permanent home in North York. In fact, this striking building located within a complex of the Ismaili Center and gardens, is the first North American museum dedicated exclusively to Islamic arts and culture.